Effects of Chinese herbal feed additives on the sperm quality and reproductive capacity in breeding boars - Tu, Weilong; Zhang, Weiyi; Wang, Hongyang; Zhang, Yingying; Huang, Ji; Li, Bushe; Li, Xin; Tan, Yongsong; Wu, Xiao (Frontiers in Veterinary Science, 2023)
Currently, Chinese herbal feed additives (CHFA) are commonly utilized in domestic pig farms.However, their impact on the sperm quality and reproductive capacity of imported breeding boars has yet to be thoroughly explored. In this study, the effect of CHFA on the sperm quality and reproductive capacity of the imported Duroc boars was investigated. Sixteen boars were randomly divided into control group and experimental (CHFA treated) group and fed normal or CHFA-levels containing diets, respectively.The sperm quality and reproductive hormone levels were periodically tested, and the reproductive capacity with breeding sows were evaluated. The results showed that the CHFA treated group boars significantly improved sperm volume, sperm concentration, and motility and reduced the sperm abnormalities. Furthermore, the serum levels of reproductive hormone such as follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone (T) in the CHFA treated group were significantly higher than those in the control group. Although there was no significant difference in the initial birth weight of piglets between the two groups, the CHFA treated group had a significantly higher average number of piglets born, the average number of piglets born alive, the number of piglets weaned at 28 days, and the weaning weight compared to the control group. These findings suggest that CHFA can significantly improve the sperm quality of breeding boars and enhance their reproductive hormone levels as well as the reproductive capacity, providing direct evidence for the further application of CHFA in the management of breeding boars in China.